CONSIDERATIONS REGARDING THE LIMITS AND EFFECTS OF THE RECOGNITION OF A FOREIGN JUDGMENT - PĂTRĂUȘ, Mihaela (International Journal of Legal and Social Order, 2022)
In this article we aimed to analyze from a theoretical and practical point of view the limits and effects of the recognition of a foreign court decision in criminal matters, in relation to the existing regulations in European and national legislation. The establishment at European level of an area of freedom, security and justice through the provisions of art. 67 of the Treaty on the Functioning of the European Union (TFEU), imposed a new approach to the entire issue of judicial cooperation in criminal matters. The research undertaken aims to highlight the interest of the European legislator, but also the national one in this segment, as well as the existing regulatory limits, with consequences in judicial practice, but also the need for the intervention of the Union legislator to give full and complete efficiency to the principle of mutual recognition of decisions foreign judicial orders pronounced by the judicial authorities of the member states.